WEB APPLICATIONS KNOWN COUNTRIES IN SOUTHEAST ASIA USING Macromedia Dreamweaver MX - SARAH KUSUMAHWATI RINA (Jurnal Sistem Informasi, 2005)
Know Your Website Creation Countries in South-East Asia Region, aims to introduce the States in Southeast Asia to the students Elementary and Secondary Schools.In the manufacture, use Macromedia Dreamweaver MX starting from stage to determine the structure of navigation, design Output page, exporting to html page, providing links on each web page, creation and insertion of animation, the management of the site pages, and how to upload to the web server. With the added animation on every page of the website, making the display more attractive.